2013
DOI: 10.1021/sc4002577
|View full text |Cite
|
Sign up to set email alerts
|

Development of Greener Multi-Responsive Chitosan Biomaterials Doped with Biocompatible Ammonium Ionic Liquids

Abstract: There is a current interest in the development of new stimuli-responsive materials using biodegradable and biocompatible molecules, mainly if biomedical applications are envisaged. In this work, chitosan (a cationic polyelectrolyte obtained from renewable resources) and two ammonium-based ionic liquids (ILs), namely, choline chloride ([Ch][Cl]) and choline dihydrogen phosphate ([Ch][DHP]), were used to develop biocompatible and biodegradable materials that can be used as improved electrical and pH-sensitive dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 68 publications
0
77
0
Order By: Relevance
“…Chitosan is a biopolymer that is completely safe for the environment. This compound is a derivative of chitin and is characterized by biodegradability, bioactivity, and biocompatibility properties [Dias et al, 2013]. The molecules consitute oligosaccharides and biopolymers found in the cell walls of some fungi [Lizárraga-Paulin et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a biopolymer that is completely safe for the environment. This compound is a derivative of chitin and is characterized by biodegradability, bioactivity, and biocompatibility properties [Dias et al, 2013]. The molecules consitute oligosaccharides and biopolymers found in the cell walls of some fungi [Lizárraga-Paulin et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan has shown to have inhibitory effect on growth of many plant pathogens [28,29]. This compound has shown properties, such as bioactivity and biocompatibility [30]. The research out come from the literature have shown that, when used in plants, chitosan can increase the yield [31], reduce transpiration [32] and induce a range of metabolic changes as a result of which, plants become more resistant to viral, bacterial and fungal infections [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that they have similar curves. The absorption peak of the β- (1)(2)(3)(4) stretching is at about 895 cm -1 , and the dissymmetry stretching vibration of the C-O-C is at about 1029 cm -1 . The peak at about 2914 cm -1 can be regarded as the -CH and -CH 2 stretching, and that at about 1134 cm -1 and 1360 cm -1 are the stretching absorption and O-H twisting.…”
Section: Characterization Of Chitosansmentioning
confidence: 99%
“…Chitosan, the deacetylated form of chitin, is composed of D-glucosamine units joined by β-(1-4) glucosidic bonds ( Figure 1) [1][2][3]. Due to its low toxicity, biocompatibility and antimicrobial activity, chitosan is widely applied in the fields of fertilizers, ion-exchange resins, membrane separation, pharmaceutics, cosmetics etc [4][5][6].…”
Section: Introductionmentioning
confidence: 99%